Development of radon detectors calibration system in Cameroon - Oumar Bobbo Modibo; Gondji Dieu Souffit; Koyang François; Ndjana Nkoulou II Joseph Emmanuel; Eka Djatnika Nugraha; Chutima Kranrod; Saïdou; Shinji Tokonami (Radiation Medicine and Protection)
Objective: To develop a radon detectors calibration system at the Research Centre for Nuclear Science and Technology (CRSTN) of the Institute of Geological and Mining Research (IRGM) in Cameroon. Methods: A transparent box named radon chamber, a certified radon source, and a reference device have been provided to Cameroon by the International Atomic Energy Agency (IAEA) within the framework of a technical cooperation project. Depending on what radon levels are expected, two different configurations (Hookup I and Hookup II) of the system are adopted. Hookup I is a closed loop, and Hookup II is an open loop that samples fresh air. Results: The operation of the system generates a radon concentration of up to ∼30,000 Bq/m3 when applied the Hookup I and of up to 1,000 Bq/m3 using the Hookup II configuration. For the calibration of the detectors for environmental radon monitoring, a stabilized concentration of 1,000 Bq/m3 is enough. Furthermore, temperature, relative humidity, and pressure, in the reference instrument ranged from 23 to 40°C, 32%–72%, and 929 to 936 mBar, respectively. Inside the radon chamber, temperature, relative humidity, and pressure are similar to the laboratory's condition. Conclusion: The present calibration system will be useful for the calibration of radon detectors. The system can also be used for various purposes such as research activities on radon, education on radon detection, radon measurement, radon mitigation, radon mapping, protection against radon, and research in the African region.